Antiphona ad Introitum dalam Missale Romanum Paulus VI: Asal Usul, Evolusi, Teologi - Watu, Christianus (Litbang STFT Widya Sasana Malang, 2024)
Antiphona ad Introitum or Entrance Antiphon is a liturgical text in the Missale Romanum. Following the liturgical renewal of the Second Vatican Council, the Entrance Antiphon’s function, form, and content underwent significant changes based on renewal criteria. Its role has shifted, and it is no longer intended for chant but exclusively for recitation. The form now consists of a single antiphon, unaccompanied by psalm verses and the doxology of the Gloria Patri. While some texts from the old Missale have been retained in their original form, most have been modified to suit their function better. This study seeks to elucidate the method of this reform, trace the editorial history of these texts, and provide a historical analysis of their origin and evolution from the early centuries to the present day. The aim is to help readers understand the background and evolution of these texts, the criteria utilized by the Consilium in the renewal, their theological significance, and their contemporary use. The conclusion of this study will underscore the dynamic nature of liturgy, constantly adapting to the needs of the times and its recipients. Ongoing updates and refinements will further enhance the congregation's comprehension of the mystery of the liturgical season. This study employs a historical-liturgical perspective through a comprehensive literature review.